Interposition Arthroplasty of the Elbow Utilizing a Lateral Epicondyle Osteotomy. Issue 2 (June 2019) - Walker, Justin W.; Merrell, Gregory A.; Reiter, Brock D.; Hastings, Hill
Abstract : Management of severe elbow arthritis in young or active patients presents a challenging problem. Interposition arthroplasty is a useful salvage procedure for these patients but has a significant failure rate associated with postoperative instability. Previous studies have sought to preserve the integrity of the medial elbow ligament complex to decrease postoperative instability and the need for external fixation. Our lateral epicondylar osteotomy technique preserves the native lateral elbow ligament complex. Potential advantages include bone-to-bone healing of the osteotomy, decreased postoperative instability, and the decreased need for and associated costs and potential complications of supplemental external fixation.